Analysis of Changes in the Meaning of Loanwords in the Modern Indonesian Corpus - Nahak, Kristofel Bere; Dapubeang, Abdul Rahim Arman Putera; Kurniawan, Muh. Ardian (Universitas Pendidikan Indonesia, 2025)
The phenomenon of changes in the meaning of loanwords in modern Indonesian occurs without adequate linguistic supervision, potentially leading to ambiguity. The urgency of this research lies in the need to map changes in meaning influenced by digital media, the social environment, and culture. The purpose of this study is to analyse the types and patterns of changes in the meaning of loanwords in the modern Indonesian corpus and to understand the perceptions of young users towards this phenomenon. The study used a descriptive qualitative approach supported by quantitative data. The sample size was 260 elementary school students in Kefamenanu City, selected purposively. Data collection techniques were carried out through corpus analysis, closed-ended surveys with a Likert scale, and structured interviews. Data analysis techniques combined descriptive statistics and thematic analysis. The results show that the meaning of words such as event, platform, and literacy has shifted significantly from their original meaning due to the influence of media and social usage. In conclusion, the meaning of loanwords is dynamic and contextual. The implications of these findings indicate the need to integrate material on changes in meaning in language learning and the development of language policies that are adaptive to the semantic developments of modern society.